Optimalisasi Sistem Pertanian Modern Poktan Sosial 3 melalui Sistem Penyiraman Otomatis Berbasis Energi Surya - Putri, Arisa Olivia; Kurniawan, Ardi; Saputra, Kalvin; Santoso, Rifaldi Wahyu; Ubaidillah, Aziz; Dianova, Brainvendra Widi (Universitas Pahlawan Tuanku Tambusai, 2026)
This community service activity aims to design and implement an automatic irrigation system based on soil moisture sensors supported by renewable energy from solar panels at the Social Farming Group 3 Baktijaya in Sukmajaya District, Depok City. The implementation methods include problem identification, system design, socialization, training, implementation, and evaluation based on quantitative surveys involving 17 group members. Evaluation results indicate that 70.6% of respondents consider the automatic irrigation system to be very helpful in land management and efficient water use, while 52.9% state that the system provides tangible economic benefits to the surrounding community. The successful implementation of this technology addressed labor limitations and improved farming productivity in an independent and sustainable manner. These findings emphasize the importance of developing modern agricultural systems based on smart technology and renewable energy as adaptive solutions to climate dynamics and changing urban agricultural needs.